Determinants Effectiveness Information Technology Governance in Higher Education Institution (HEI) using partial least squares structural equation modeling approach (PLS-SEM) - Anwar, Fattah; Resad, Setyadi (2021)
Information technology supports the achievement of business organization objectives. The Higher Education institution is a business organization engaged in the field of education. Effective IT governance will ensure alignment between IT and business goals. Organizations with ineffective IT governance will suffer due to poor performance of IT resources such as inaccurate information quality, inefficient operating costs, runaway IT project and even the demise of its IT department. This study seeks to examine empirically the individual IT governance mechanisms that influence the overall effectiveness of IT governance. Furthermore, this study examines the relationship of effective IT governance and IT Innovation within the Higher education organizations. The sampling technique to be carried out in this study is a multi-stage purposeful random sampling. In sequence, researchers will combine surveys through online. The quantitative data were analyzed by the smallest partial quadratic structural equation method (PLS-SEM) using Smart PLS 3.0. The results obtained from this dataset show a positive significant relationship between effective IT governance and the following mechanisms: IT Steering Committee, Involvement of Senior management in IT, and Organizational Communication System. Also a positive relationship between ITG Effectiveness within IT Innovation. Organizational Communication System and IT Innovation have a positive significant relationship, and negative relationship with insignificant for Organizational Performance Measurement System.